Incidencia de las actividades del laboratorio de química general del área agroindustrial en la seguridad y salud ocupacional de los trabajadores - Cedeño Vélez, Víctor Alfonso (2016)
The research focuses in the Security and Occupational Health of workers in the General Chemistry Lab of the Agroindustrial area in the ESPAM-MFL, with the purpose of identifying and valuing the factors of (physical) risks, like noise, lighting and temperature, and offer a Security and Occupational Health Plan an idea that will make it possible to mitigate the risk. There should exist a suitable environment in which the workers sit down coolly and well-being. The research techniques were; observation, interview, survey, and the triple counterfoil criterion (an important tool in the research); in addition they allowed to analyze the current situation of the study area. The method of research was qualitative inductive. Obtaining favorable results across the interview and survey realized to the technical personnel and teachers who work in the Laboratory then value the factors of risk. The triple counterfoil criterion gave a moderate Risk rate. Finally, offer the plan to the authorities whose intention is to applied in the facilities of the General Chemistry Lab being great importance for the personnel that works there, same for the students realizing their academic practices.